Primary immunodeficiencies: HSCT experiences of a single center in Turkey. (6th June 2021) - Erol Cipe, Funda; Adakli Aksoy, Basak; Aydogdu, Selime; Dikme, Gurcan; Kiykim, Ayca; Aydogmus, Cigdem; Yucel, Esra; Bozkurt, Ceyhun; Fisgin, Tunc
Abstract: Background: Primary immunodeficiency diseases (PID) are characterized by the occurrence of frequent infections and are caused by many genetic defects. Hematopoietic stem cell transplantation (HSCT) is the only curative treatment option for the majority of PID. As a Pediatric Hematology‐Oncology‐Immunology Transplantation Unit, we wanted to present our HSCT experience regarding treatment of primary immunodeficiency diseases. Methods: 58 patients were included in the study between January 2014 and June 2019. We searched 9/10 or 10/10 matched‐related donor (MRD) firstly, in the absence of fully matched‐related donor. We screened matched unrelated donor (MUD) from donor banks. MRD was used in 24 (41.3%) patients, MUD in 20 (34.4%) patients, and haploidentical donors in 14 (24.1%) patients. Demographic data, HSCT characteristics, and outcome were evaluated. While 16 patients had severe combined immunodeficiency (SCID), the remaining was non‐SCID. Results: Of the 58 patients, 38 were male and 20 were female. Median age at transplantation was 12 months (range: 2.5–172 months). Combined immunodeficiencies consisted 67.2% of patients. Mean follow‐up time was 27 months (6 months–5 years). Median neutrophil, lymphocyte, and thrombocyte engraftment days were similar in comparison of both donor type and stem cell source. The most common complication was acute GvHD in 15 (25.8%) patients. In total, five patients (31%) belonging to the SCID group and 10 patients (23.8%) belonging to the non‐SCID group died. Our total mortality rate was 15 (25.8%) in all patients. Conclusions: We would like to present our HSCT experiences as a pediatric immunology transplantation center. Existing severe infections before transplantation period, BCGitis, and CMV are important issues of transplantation in Turkey. However, the follow‐up time is shorter than some studies, our results regarding complications and survival are similar to previous reports.